Business Model Canvas Analysis of Hale’s Blue Boy: Market Strategy, Consumer Trends, and Competitive Challenges - Klinthong, Nachakamol; Viwatthammakul, Piyaphat; Krapookthong, Maichanok; Panthanapratez, Thanapat; Robkit, Achareeya (วารสารพัฒนาธุรกิจและอุตสาหกรรม, 2025)
Hale’s Blue Boy has led the Thai-flavored syrup market for over 60 years with strong brand equity, superior-quality ingredients, and a secret formula. A Business Model Canvas (BMC) analysis was conducted to assess its strategic approach, key success factors, and potential areas for future development. Its key customers include dessert shops, families, and sweet flavor lovers. Its strength lies in its unique taste, premium glass packaging, and nostalgic emotional appeal. Hale’s Blue Boy uses a multi-channel distribution system via hypermarkets, convenience stores, and traditional retailers for widespread market penetration. The company builds customer loyalty through taste and product quality consistency, and uses Collaborative Planning, Forecasting, and Replenishment (CPFR) to coordinate with partners. Sales of syrups are the major revenue source, underpinned by brand strength and product consistency. Hale’s Blue Boy is faced with the threat of shifting consumer preference for healthy products and growing competition. The study recommends long-term sustainability initiatives such as diversification into healthier foods, eco-friendly packaging, and online interaction with younger consumers. Having reliance on a single category of products is risky. It requires innovation and flexibility to stay competitive.